Analysis of Hotspots and Trends of Life Insurance in China - Fangxiang CHENG; Xindi WANG (Communications of International Proceedings, 2020)
With the continuous development of economy, China has already become the world's second largest life insurance market. In order to have a deep insight of the research hotspots and trend in the field of life insurance in China, this article analyzes 1,389 related articles of core journals, which were published from 2000 to 2019. This paper firstly analyzes the research status of life insurance in China from the perspectives of quantity evolution, the most cited articles, and the distribution of journal and institution, as well as the hotspot map of articles. Next, this research obtains the hot topics and trend in life insurance research by the frequency of keywords, co-word networks and the method of network modularization. These hot topics are life insurance market and products, life insurance company operation, life insurance finance and life insurance business processing. Finally, the trend analysis shows that life insurance company operation has the hottest trend in recent years.
Keywords: Bibliometrics; Life insurance; Research hotspots; Co-word analysis